Analisis Implementasi Integrasi Jamsoskes Sumatera Selatan Semesta ke Program Jaminan Kesehatan Nasional di Kota Palembang dari Sisi Stakeholder - Melisa Yuni Nirmalasari; Dian Safriantini (Jurnal Kebijakan Kesehatan Indonesia, 2019)
Backgound: Based on Presidential Regulation No. 82 of 2018, regional governments that carry out the Regional Health Insurance are obliged to integrate it into JKN (National Health Insurance) Program held by the BPJS (Health Insurance Organizing Agency). Similarly, the Government of South Sumatra Province has suspended the Jamsoskes Sumatera Selatan Semesta Program commercing January 1, 2019 by issuing Circular Letter Number 057/DINKES/SE/2018. This study aimed to analyze the integration implementation of Jamsoskes Sumatera Selatan Semesta into the JKN Program in Palembang City.  Method: This study used qualitative approach through in-depth interviews, literature review and field observations. There were 7 informants selected by purposive technique carry out at the Public Health Office, BPJS Health, Social Service, and Puskesmas (Community Health Center).Result: Communication (Transmission, Clarity and Consistency) in implementing the were carried out quite well because each relevant agency had followed up the Circular Letter and disseminated the information clearly and consinstently to the implementing unit underneath it. Resource, there were still obstacles in the form of funds and limited data poor. Disposition, all parties involved in the integration supported this integration. Bureaucratic Structure, there was no Standard Operational Procedure (SOP) at several relevant agencies to carry out the integration. Distribution of responsibilities was carried out by means of stakeholder coordination meetings.Conclusion: The integration still faces obstacles in the form of limited funds to cover people who have not received health insurance and poor popilation data that has not been verified and validated so that the social service needs to directly improve the community data by conducting data collection on poor people in the Palembang city. Keywords: Integration, Jamsoskes, Nasional Health Insurance